2023
DOI: 10.1017/s2040174423000399
|View full text |Cite
|
Sign up to set email alerts
|

Maternal pea fiber supplementation to a high calorie diet in obese pregnancies protects male offspring from metabolic dysfunction in adulthood

Gabriella A. Andreani,
Saleh Mahmood,
Mulchand S. Patel
et al.

Abstract: We investigated the influence of maternal yellow-pea fiber supplementation in obese pregnancies on offspring metabolic health in adulthood. Sixty newly-weaned female Sprague-Dawley rats were randomized to either a low-calorie control diet (CON) or high calorie obesogenic diet (HC) for 6-weeks. Obese animals were then fed either the HC diet alone or the HC diet supplemented with yellow-pea fiber (HC + FBR) for an additional 4-weeks prior to breeding and throughout gestation and lactation. On postnatal day (PND)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…This may be attributed to the limited impact of the intervention on maternal obesity. However, in a similar rat model, we have recently reported that the supplementation of an obesity-inducing maternal diet with yellow pea protein [30] and fiber [29] fractions throughout pregnancy improved the metabolic health of offspring independent of a change in maternal obesity status.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This may be attributed to the limited impact of the intervention on maternal obesity. However, in a similar rat model, we have recently reported that the supplementation of an obesity-inducing maternal diet with yellow pea protein [30] and fiber [29] fractions throughout pregnancy improved the metabolic health of offspring independent of a change in maternal obesity status.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, the objectives of this study were to assess whether black bean powder (BBP) supplementation to mothers (throughout pre-pregnancy, gestation, lactation) or to pre-programmed male offspring would offer protection against obesity and associated metabolic dysfunction (i.e., dyslipidemia and hepatic steatosis) in adult offspring. We chose to only examine male offspring in this study as we have previously reported that female offspring are largely resistant to the metabolic programming influence of maternal obesity in this model with respect to the study outcomes [29,30].…”
Section: Introductionmentioning
confidence: 99%